Rabbit-ATG or basiliximab induction for rapid steroid withdrawal after renal transplantation (Harmony): an open-label, multicentre, randomised controlled trial. Issue 10063 (17th December 2016) - Thomusch, Oliver; Wiesener, Michael; Opgenoorth, Mirian; Pascher, Andreas; Woitas, Rainer Peter; Witzke, Oliver; Jaenigen, Bernd; Rentsch, Markus; Wolters, Heiner; Rath, Thomas; Cingöz, Tülay; Benck, Urs; et al.
Summary: Background: Standard practice for immunosuppressive therapy after renal transplantation is quadruple therapy using antibody induction, low-dose tacrolimus, mycophenolate mofetil, and corticosteroids. Long-term steroid intake significantly increases cardiovascular risk factors with negative effects on the outcome, especially post-transplantation diabetes associated with morbidity and mortality. In this trial, we examined the efficacy and safety parameters of rapid steroid withdrawal after induction therapy with either rabbit antithymocyte globulin (rabbit ATG) or basiliximab in immunologically low-risk patients during the first year after kidney transplantation. Methods: In this open-label, multicentre, randomised controlled trial, we randomly assigned renal transplant recipients in a 1:1:1 ratio to receive either basiliximab induction with low-dose tacrolimus, mycophenolate mofetil, and steroid maintenance therapy (arm A), rapid corticosteroid withdrawal on day 8 (arm B), or rapid corticosteroid withdrawal on day 8 after rabbit ATG (arm C). The study was done in 21 centres across Germany. Only participants aged between 18 and 75 years with a low immunological risk who were scheduled to receive a single-organ renal transplant from either a living donor or a deceased donor were considered for enrolment. Patients receiving a second renal transplant were eligible, provided that the first allograft was not lost due to acute rejection within the first year after transplantation. Donor and recipient had to be ABO compatible. Grafts with pre-transplant existing donor-specific human leukocyte antigen (HLA) antibodies were not eligible and the recipients had to have a panel-reactive antibody concentration of 30% or less. Pregnant women and nursing mothers were excluded from the study. The primary endpoint was the incidence of biopsy-proven acute rejection (BPAR) at 12 months. All analyses were done by intention-to-treat. This trial is registered withClinicalTrials.gov, numberNCT00724022 . Findings: Between Aug 7, 2008, and Nov 30, 2013, 615 patients were randomly assigned to arm A (206), arm B (189), and arm C (192). BPAR rates were not reduced by rabbit ATG (9·9%) compared with either treatment arm A (11·2%) or B (10·6%; A versus C: p=0·75, B versus C p=0·87). As a secondary endpoint, rapid steroid withdrawal reduced post-transplantation diabetes in arm B to 24% and in arm C to 23% compared with 39% in control arm A (A versus B and C: p=0·0004). Patient survival (94·7% in arm A, 97·4% in arm B, and 96·9% in arm C) and censored graft survival (96·1% in arm A, 96·8% in arm B, and 95·8% in arm C) after 12 months were excellent and equivalent in all arms. Safety parameters such as infections or the incidence of post-transplantation malignancies did not differ between the study arms. Interpretation: Rabbit ATG did not show superiority over basiliximab induction for the prevention of BPAR after rapid steroid withdrawal within 1 year after renal transplantation. Nevertheless, rapid steroid withdrawal after induction therapy for patients with a low immunological risk profile can be achieved without loss of efficacy and is advantageous in regard to post-transplantation diabetes incidence. Funding: Investigator Initiated Trial; financial support by Astellas Pharma GmbH, Sanofi, and Roche Pharma AG.